2018
DOI: 10.3233/cbm-170767
|View full text |Cite
|
Sign up to set email alerts
|

miR-30a-5p together with miR-210-3p as a promising biomarker for non-small cell lung cancer: A preliminary study

Abstract: The present preliminary study demonstrated that five tested miRNAs were deregulated in cancer tissue. Moreover, miR-30a-5p together with miR-210-3p with excellent sensitivity and acceptable specificity may distinguish cancer tissue form non-cancerous tissue and thus may become a potential diagnostic biomarker for NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 63 publications
1
30
0
1
Order By: Relevance
“…miR-30a has been found to be one of the downregulated miRNAs in various types of solid tumors. Many studies have proved that the expression level of miR-30a-5p in NSCLC cells and tissues is significantly downregulated compared to that in normal lung cells [18][19][20][21], which is consistent with the results of the present study. miR-30a-5p has been found regulating tumor development by inhibiting oncogenes in various tumors [19,22,23], and it can enhance the sensitivity of NSCLC to paclitaxel by targeting BCL-2 expression [24].…”
Section: Discussionsupporting
confidence: 93%
“…miR-30a has been found to be one of the downregulated miRNAs in various types of solid tumors. Many studies have proved that the expression level of miR-30a-5p in NSCLC cells and tissues is significantly downregulated compared to that in normal lung cells [18][19][20][21], which is consistent with the results of the present study. miR-30a-5p has been found regulating tumor development by inhibiting oncogenes in various tumors [19,22,23], and it can enhance the sensitivity of NSCLC to paclitaxel by targeting BCL-2 expression [24].…”
Section: Discussionsupporting
confidence: 93%
“…miR‐30a has been shown to play an inhibitory role in many cancers, such as cancers of the colon, breast, and lung 38‐40 . miR‐30a has also been previously reported to function as a tumor suppressor in PCa 12,13,15,16,41 .…”
Section: Discussionmentioning
confidence: 98%
“…Subsequently, we analyzed the relationship between five differentially expressed miRNAs and OS, and found that the expression level of hsa-mir-210 was significantly correlated with OS [34,35], however, the relationship between the expression of hsa-mir-210 and the survival of LUSC has rarely been reported. In this study, we obtained through KM survival analysis that the overall survival of patients with low expression of hsa-mir-210 was significantly prolonged in the higher expression group, and the difference between the two groups was statistically significant (P=0.…”
Section: Discussionmentioning
confidence: 99%